1977
DOI: 10.2466/pms.1977.45.3f.1179
|View full text |Cite
|
Sign up to set email alerts
|

Typewriting Rate as a Function of Reaction Time

Abstract: This study was designed to determine the relationship between reaction time and typewriting rate. Subjects were 24 typists ranging in age from 19 to 39 yr. Reaction times (.001 sec) to a light were recorded for each finger and to each alphabetic character and three punctuation marks. Analysis of variance yielded significant differences in reaction time among subjects and fingers. Correlation between typewriting rate and average reaction time to the alphabetic characters and three punctuation marks was --.75. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…Second, I calculated the correlation between the Simon effect and mean RT across all conditions of the experiments. Mean RT reflects typing skill (Hayes, Wilson, & Schafer, 1977). The correlations between mean RT and speed on the typing test were significant in each experiment (for Experiments 1 and 2, r s = −.720 and −.553 and F s[1, 15] = 16.10 and 6.60, respectively [both p s <.05]; for Experiment 3, r s = −.628, −.604, and −.646, and F s[1, 15] = 9.78, 8.63, and 10.77, for LEFT-right, LEght-riFT, and Light-rEFT words, respectively [all p s <.01]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, I calculated the correlation between the Simon effect and mean RT across all conditions of the experiments. Mean RT reflects typing skill (Hayes, Wilson, & Schafer, 1977). The correlations between mean RT and speed on the typing test were significant in each experiment (for Experiments 1 and 2, r s = −.720 and −.553 and F s[1, 15] = 16.10 and 6.60, respectively [both p s <.05]; for Experiment 3, r s = −.628, −.604, and −.646, and F s[1, 15] = 9.78, 8.63, and 10.77, for LEFT-right, LEght-riFT, and Light-rEFT words, respectively [all p s <.01]).…”
Section: Discussionmentioning
confidence: 99%
“…Mean RT reflects typing skill (Hayes, Wilson, & Schafer, 1977 . In Experiment 1, the correlation between the Simon effect and mean RT was positive (r ϭ .210) and nonsignificant, F(1, 15) Ͻ 1.…”
Section: The Simon Effect and Typing Skillmentioning
confidence: 99%
“…18 to +.44, in tapping tasks (e.g., Borkan & Norris, 1980;Dirken, 1972;Furukawa et al, 1975;Jalavisto, 1965); and correlations of .42 to .53, in other visual-manual transcription tasks such as the digit-symbol substitution task (see Salthouse, 1982b, for a review). Several studies have reported that one or more of these measures is related to speed of typing (e.g., Ackerson, 1926;Book, 1924;Cleaver & O'Connor, 1982;Flanagan & Fivars, 1964;Flanagan, Fivars, & Tuska, 1959;Hayes, 1978;Hayes, Wilson, & Schafer, 1977;Leonard & Carpenter, 1964;Muscio & Sowton, 1923;Tuttle, 1923), although there are some contradictory results (e.g., Hansen, 1922). The RT analogy, therefore, still seems relevant, even though the quantitative estimates should not be taken too seriously.…”
Section: Age Effectsmentioning
confidence: 99%
“…The simplified typing task used in Experiment 1 was letter reaction time, which measured latency to type a single letter. Previous studies using this task found that performance is related to typing skill, with more skilled typists having faster reaction times (Hayes, 1978;Hayes, Wilson, & Schafer, 1977). The task used in Experiment 2 was digraph typing, a digraph referring to two successive keystrokes.…”
mentioning
confidence: 99%